Perspective of Humanistic Psychology Hierarchy of Needs: Loneliness of Adolescents Living in Orphanages - Octavinna Deavy; Diah Karmiyati (International Conference on Psychology and Education (ICPE), 2024)
Loneliness can lead to severe issues that adversely affect the mental and physical health of adolescents. Loneliness in adolescents living in orphanages tends to be higher than in adolescents living with their families. This can cause them to have negative expectations of the future and put them at risk. Loneliness can also affect adolescents’ social anxiety, delinquency, aggression and depression. This paper is library research on the phenomenon of loneliness in adolescents living in orphanages studied through the Abraham Maslow-Hierarchy of Needs humanistic approach.  The results show that of the five hierarchies of human needs, the needs are met at the level of physiological needs and safety needs. Unmet needs are love and belonging needs, self-esteem needs and self-actualization needs. The review found that it is necessary to increase the need for affection to be able to go towards self-esteem needs and self-actualization needs.